Empatia em camundongos: avaliação do papel da amídala, insula e córtex cingulado anterior na nocicepção em camundongos expostos ao teste de contorções abdominais - Costa, Vinícius Pelarin do Nascimento (2014)
Empathy can be defined as the capacity for perceive emotional signals from others. Among these signals, the ability to perceive pain has clear adaptive and evolutionary value. Pain can be defined as a subjective experience that includes sensorial, emotional and cognitive components. Evidence has emphasized the role of amygdala, anterior cingulate cortex (ACC) and insula in modulation of pain and empathy. Research indicates the capacity of rodents to express empathy to a conspecific in pain or suffering. Works from literature and finds from our laboratory demonstrated that living together with a cagemate is able to alter the nociceptive behavior in mice. However, there are no works evidencing if occur alterations in nociception by living together with a cagemate with chronic pain and which encephalic structures would be involved in this modulation. To overcome this, male Swiss-albino mice were housed in groups or in pairs. The role of amygdala, ACC and insula are accessed by non-selective inactivation with cobalt chloride (CoCl2). Mice housed in groups (Experiment 1), aging 6-8 weeks, underwent a stereotaxic surgery. 4 to 5 days after surgery, these animals received saline or CoCl2 microinjection, and, after 10 minutes, they were submitted to the writhing test during 5 minutes (acetic acid 0.6%, i.p., nociceptive stimulus). On the dyads (Experiment 2), animals lived together for 28 days since weaning. On the 14th day, one animal of each pair were submitted to a sciatic nerve constriction (SNC animal) or not (sham animal). On the 24th day, the cagemate underwent a stereotaxic surgery, and, on the 28th day, they were submitted to the writhing test after microinjection of saline or CoCl2, like the procedure described to Experiment 1. To Experiment 1 were utilized Student s t test to independent samples; to Experiment 2 were utilized two-way analysis of variance (ANOVA; living together x treatment). Duncan s multiple range tests were utilized as post hoc. A p value of 0.05 or less was required for significance in both experiments. In Experiment 1, inactivation of the amygdala increased the number of writhing, while inactivation of ACC and insula did not alter this measure, suggesting a distinct modulatory role of these structures on the sensorial compound of pain. Our results demonstrated that for the mice that lived in groups, while inactivation of the ACC and insula did not change writhing, inactivation of amygdala increased it, suggesting a distinct modulatory role of these structures on sensory component of pain in the writhing test. In Experiment 2, living together with a SNC-cagemate increased writhing on the pair, suggesting that this experience activates the circuitry of neural representation of pain on the observer mouse (state of priming ). Thus, when this animal experienced nociception, its response was exacerbated. In this condition, inactivation of insula and amygdala produces opposite results, i.e., decreased and increased in contortions in those animals that lived together with a SNC animal, respectively. ACC inactivation did not alter writhing behavior. In this sense, our results suggest a different modulatory role of these structures on cognitive, affective-emotional and sensorial components of pain, and on empathy for pain.